Proceedings of the 1st Symposium on Applied Perception in Graphics and Visualization 2004
DOI: 10.1145/1012551.1012557
|View full text |Cite
|
Sign up to set email alerts
|

Distance perception in real and virtual environments

Abstract: Two experiments were conducted to compare distance perception in real and virtual environments. In Experiment 1, adults estimated how long it would take to walk to targets in real and virtual environments by starting and stopping a stopwatch while looking at a target person standing between 20 and 120 ft away. The real environment was a large grassy lawn in front of a university building. We replicated this scene in our virtual environment using a nonstereoscopic, large screen immersive display system. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
88
5
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 17 publications
10
88
5
2
Order By: Relevance
“…A disadvantage is that the action is imagined instead of performed, which involves potentially confounding mental processes. However, Decety et al [4] and Plumert et al [14] compared blind walking and timed walking to real-world targets, and found excellent accuracy for both methods.…”
Section: Distance Perception Measurement Protocolsmentioning
confidence: 99%
See 4 more Smart Citations
“…A disadvantage is that the action is imagined instead of performed, which involves potentially confounding mental processes. However, Decety et al [4] and Plumert et al [14] compared blind walking and timed walking to real-world targets, and found excellent accuracy for both methods.…”
Section: Distance Perception Measurement Protocolsmentioning
confidence: 99%
“…Another shortcoming of blind walking, which relates to the experiment reported here, is that it cannot be used to indicate a depth judgment in a large-screen immersive display, because there is not enough room to blindly walk to a target that is located beyond the display's screen. Plumert et al [14] and Ziemer et al [20] used timed walking to measure distance judg- ments in a CAVE. Perceptual matching has also been used in virtual environments (e.g., [5,16,18,19]); Bodenheimer et al [2] used perceptual bisection to measure distance judgments in virtual and real-world environments.…”
Section: Measurement Protocols In Virtual Environmentsmentioning
confidence: 99%
See 3 more Smart Citations